THE IMPACT OF TOP MANAGEMENT SUPPORT AND ORGANIZATIONAL STRUCTURE ON ACCOUNTING INFORMATION SYSTEMS QUALITY - Darma, Jufri; Nurwendari, Weny; Sriwedari, Tuti; Herliani, Rini (Department of Accounting, Faculty of Economics & Business, 2024)
This study aimed to investigate how the quality of accounting information systems in higher education institutions in North Sumatra is influenced by the organizational structure and the support from top management. A survey involving 67 participants, who are users of accounting information systems at colleges in North Sumatra, was conducted. Data was gathered through the administration of a questionnaire. The collected data was analyzed using Structural Equation Modeling with a Partial Least Square approach, utilizing the Smart-PLS software. The findings of the study provided empirical evidence indicating that both top management support and organizational structure significantly impact the quality of accounting information systems in higher education institutions located in North Sumatra.